Current status of grapevine trunk disease pathogens on asymptomatic nursery-produced grapevines in Türkiye - AKGÜL, Davut Soner; GÜNGÖR SAVAŞ, Nurdan; YILDIZ, Murat; BÜLBÜL, İzzet; ÖZARSLANDAN, Mümine (Phytopathologia Mediterranea, 2023)
Good health of grapevine plants is important for productivity and sustainability of newly established vineyards, and accurate detection of bacterial and fungal pathogens is a prerequisite for managing the diseases they cause in nurseries. This study screened marketable, bare-rooted grapevine plants, obtained from different geographical regions of Türkiye, for fungal pathogens associated with grapevine trunk diseases (GTDs). In 2021, 43 grapevine nurseries located in eight provinces were surveyed to reveal the status of GTD pathogens on asymptomatic marketable plants. Fungal pathogens isolated from the roots and basal parts of asymptomatic dormant grapevines were identified using with morphological characteristics and molecular markers, and were subjected to pathogenicity tests. Six species; Cytospora viticola, Diaporthe ampelina, Diplodia seriata, Lasiodiplodia brasiliensis, Neofusicoccum parvum, and Truncatella angustata (associated with dieback), and six species; Cadophora ferruginea, Cadophora luteo-olivacea, Cadophora malorum, Phaeoacremonium minimum, Phaeoacremonium tuscanicum and Phaeomoniella chlamydospora (associated with Petri disease) were identified based on DNA sequencing of ITS and TEF1-α genes. GTD pathogens were detected in 12 and 14 of the 43 nurseries, respectively. Pathogenicity tests on 1103P vines revealed that all species were pathogenic (N. parvum and C. luteo-olivacea being the most virulent), and caused significant wood necroses when compared to non-inoculated experimental controls. This is the first report of C. ferruginea, C. malorum, L. brasiliensis, and P. tuscanicum associated with GTDs in Türkiye.